(untitled) (Journal of Parents and Teachers, 2014)
This article offers a historical and legal review of the subject of religion. Through the review of various laws, from the 1978 Constitution to the LOCE, explains the role and the reason of the existence of the subject of religion in schools. In addition, the problem of teachers of religion in public schools is also treated here.